Establishing the interplay between lean operating and continuous improvement routines: a process view. Issue 13 (9th August 2022) - Knol, Wilfred H.; Lauche, Kristina; Schouteten, Roel L.J.; Slomp, Jannes
Abstract : Purpose: Building on the routine dynamics literature, this paper aims to expand our philosophical, practical and infrastructural understanding of implementing lean production. The authors provide a process view on the interplay between lean operating routines and continuous improvement (CI) routines and the roles of different actors in initiating and establishing these routines. Design/methodology/approach: Using data from interviews, observations and document analysis, retrospective comparative analyses of three embedded case studies on lean implementations provide a process understanding of enacting and patterning lean operating and CI routines in manufacturing SMEs. Findings: Incorporating the "who" and "how" next to the "what" of practices and routines helps explain that rather than being implemented in isolation or even in conjunction with each other, sustainable lean practices and routines come about through team leader and employee enactment of the CI practices and routines. Neglecting these patterns aligned with unsustainable implementations. Research limitations/implications: The proposed process model provides a valuable way to integrate variance and process streams of literature to better understand lean production implementations. Practical implications: The process model helps manufacturing managers, policy makers, consultants and educators to reconsider their approach to implementing lean production or teaching how to do so. Originality/value: Nuancing the existing lean implementation literature, the proposed process model shows that CI routines do not stem from implementing lean operating routines. Rather, the model highlights the importance of active engagement of actors at multiple organizational levels and strong connections between and across levels to change routines and work practices for implementing lean production.